Isolasi Mandiri dalam Islam: Kritik Metodologis Fatwa LBM PWNU Jawa Tengah tentang Anjuran Isolasi saat Wabah: Isolasi Mandiri dalam Islam: Kritik Metodologis Fatwa LBM PWNU Jawa Tengah tentang Anjuran Isolasi saat Wabah - Nurdin, Nazar; Bintarawati, Fenny; Nihayah, Ulfatun (Journal of Islamic Law, 2021)
This article intends to examine the recommendation to self-isolate infected with the plague within the framework of Islamic law. The study will focus on the fatwa on the LBM PWNU Jawa Tengah allowance of isolation. Isolation is an effective way of preventing the spread of the plague, reducing the number of infections. Isolation requires people to stay at home, not work or travel to public places. Even though there were isolation violations, the isolation policy was sufficient to reduce the infection rate in an area. Islam allows isolation to protect the human soul because it is part of the purpose of Islamic law. This paper is qualitative research written with a normative approach. The research data comes from library materials. The primary data source is the LBM PWNU Jawa Tengah fatwa regarding the recommendation for independent isolation, and the secondary data comes from books, journals, or other scientific publications related to research topics. After the data was collected, the analysis was carried out using a qualitative descriptive method. This study found that the opinion of Islamic law regarding the permissibility of isolation can be recommended as an effort to control infectious diseases. However, the result of this formula is not strong enough methodologically because it is sufficient to follow the opinion of jurists in standardized books. For legal opinion to be stronger methodologically, more efforts are needed to search for legal opinions to capture the meaning of the message according to the times.